Hubungan Tingkat Pendidikan Dengan Derajat Depresi Pasien Diabetes Tipe II Di RSUD Dr. Rivai Berau Kalimantan Timur - Sativa, Oryza; , Prof. Dr. Mohammad Fanani, dr. Sp. Kj (K); , dr. Erna Herawati, Sp. K.J (2015)
Background: Diabetes mellitus type II is a chronic disease prevalence is increasing in the world. People with diabetes are more prone to experience the feeling of disorder is depression. Depression is a group of disorders that are included in the mood disorders that result in decreased quality of life as well as trigger, aggravate or slow down a person's physical illness. Education will contribute to health behavior change through knowledge. Knowledge which is influenced by the level of education are contributing factors to influence a person's decision to adopt healthy behaviors. Research Purposes: This study aimed to determine the relationship of the level of education with the degree of depression of patients with diabetes mellitus type II in hospitals Dr. Rivai Berau in East Kalimantan. Methods: This study used analytic observational study with cross sectional sample of type II diabetes mellitus patients undergoing outpatient. Test is used to determine the level of education and degree of depression in this study is the Spearman test. Results: From the results of data processing was found (r = -0.775) with p < 0.001 that there is a highly significant negative correlation between level of education and the degree of depression of patients with diabetes mellitus type II. Conclusion: There is a strong negative correlation between level of education and the degree of depression of patients with diabetes mellitus type II. The higher the education level, the lower the degree of depression of patients with diabetes mellitus type II.